2019
DOI: 10.1002/hep.30252
|View full text |Cite
|
Sign up to set email alerts
|

NLR Family Pyrin Domain‐Containing 3 Inflammasome Activation in Hepatic Stellate Cells Induces Liver Fibrosis in Mice

Abstract: The NLRP3 inflammasome plays an important role in liver fibrosis development. However, the mechanisms involved in NLRP3-induced fibrosis are unclear. Our aim was to test the hypothesis that the NLRP3 inflammasome in hepatic stellate cells (HSC) can directly regulate their activation and contribute to liver fibrosis. Primary HSC isolated from WT, Nlrp3 , or Nlrp3 knock-in crossed to inducible (estrogen receptor Cre - CreT) mice were incubated with LPS and ATP, or 4OH-tamoxifen, respectively. HSC-specific Nlrp3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 34 publications
9
101
0
Order By: Relevance
“…Besides, the expression levels of brosis-related proteins in CF were also increased. Moreover, recent study showed that the activation of NLRP3-in ammasome in the hepatic stellate cells (HSCs) due to LPS could promote liver brosis also con rmed our ndings [42]. The NLRP3-in ammsome is mainly distributed in macrophage and CF, but less in CM [43], and it can interact with different types of cells [44].…”
Section: Discussionsupporting
confidence: 86%
“…Besides, the expression levels of brosis-related proteins in CF were also increased. Moreover, recent study showed that the activation of NLRP3-in ammasome in the hepatic stellate cells (HSCs) due to LPS could promote liver brosis also con rmed our ndings [42]. The NLRP3-in ammsome is mainly distributed in macrophage and CF, but less in CM [43], and it can interact with different types of cells [44].…”
Section: Discussionsupporting
confidence: 86%
“…This study established a new field of application for the licensed anti-tumor drug epirubicin as an anti-inflammatory agent, reducing IL-1β and TNF-α release from macrophages when used at low-doses. Given the increasingly recognized role of NLRP3 for the development of liver injury and fibrosis [6,8,10,11], therapeutic interventions focusing on the epigenetic programming of immune cells and the organ-specific inhibition of inflammasomes represent novel anti-inflammatory strategies, which need to be further investigated in the context of fibrogenesis. Furthermore, the anti-inflammatory properties of epirubicin may be an adverse effect in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that wild type mice develop more severe liver fibrosis induced by carbon tetrachloride (CCL 4 ) as compared to the NLRP3 −/− and ASC −/− mice, as evidenced by higher α-SMA expression and more Sirius Red staining area in the wild-type than in the knockout mice (Watanabe et al, 2009). Conversely, the activation of NLRP3 inflammasome in mice facilitates the pathological process of liver inflammation and fibrosis (Inzaugarat et al, 2019). Activated caspase-1, IL-18, and IL-1β signaling are also pivotal to the development of liver fibrosis resulting from the activation of NLRP3 inflammasome.…”
Section: Nlrp3 Inflammasome In Liver Fibrosis/cirrhosismentioning
confidence: 99%